2017
DOI: 10.1038/s41598-017-02053-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased stem cells delivered using a silk gel/scaffold complex for enhanced bone regeneration

Abstract: The low in vivo survival rate of scaffold-seeded cells is still a challenge in stem cell-based bone regeneration. This study seeks to use a silk hydrogel to deliver more stem cells into a bone defect area and prolong the viability of these cells after implantation. Rat bone marrow stem cells were mingled with silk hydrogels at the concentrations of 1.0 × 105/mL, 1.0 × 106/mL and 1.0 × 107/mL before gelation, added dropwise to a silk scaffold and applied to a rat calvarial defect. A cell tracing experiment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…This complete coverage could be explained by the honeycomb pattern's promotion of extracellular matrix synthesis and upregulation of type II collagen (Eniwumide et al, 2014). Alternatively, it might be due to the high seeding density—a strategy known to have delivered more cells while preserving the latter's viability and functions in vivo (Ding et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This complete coverage could be explained by the honeycomb pattern's promotion of extracellular matrix synthesis and upregulation of type II collagen (Eniwumide et al, 2014). Alternatively, it might be due to the high seeding density—a strategy known to have delivered more cells while preserving the latter's viability and functions in vivo (Ding et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al. adapted a hybrid approach, whereby SF hydrogels were used to deliver rat MSCs to a SF scaffold [380] . In vivo analysis in a calvarial defect found that encapsulated cells were still viable and actively participating in new bone formation 8 weeks after implantation.…”
Section: Materials Used Within Bone Tissue Engineeringmentioning
confidence: 99%
“…This is in line with the possibility that MSCs confined in the interior of these hydrogels have cytoskeletal aberrations incompatible with normal growth. In relation to silk, a previous study reported that MSCs survive for up to 10 days in culture when encapsulated in SF hydrogels while they have a moderate proliferation rate 56 . Parallel studies have examined the effect of SF stiffness on MSCs survival, finding that MSCs viability inside SF hydrogels is drastically reduced at polymer concentrations higher than 4–6% 31,32 .…”
Section: Discussionmentioning
confidence: 99%